(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, the pedagogical and psychological features of increasing the social activity of students by means of folk pedagogy are highlighted, and the importance of their role in educating young students to become socially active is discussed. Materials related to folk pedagogy can easily be compared to the ocean. We considered this study to be only a prelude and we set ourselves the goal of introducing our people to it with some of its pages taken from this ocean. Designed for many volumes and long years — Uzbek folk pedagogy requires a lot of effort and team work.